Genetic Variability and Character Association among Seed Traits of’ Madhuca latifolia Macr. - Divakara, B. N.; Sinha, Animesh; Alur, Ashok (Indian Forester, 2011)
Variability studies of twenty-three candidate plus trees of M. latifolia Macb. revealed significant difference among candidate plus trees for seed traits and germination capacity. CPT-5, CPT-16 and CPT-2 recorded highest for 100-seed weight (286.27 g), oil content (51.15 %) and germination capacity (84.77 %) respectively. The phenotypic and genotypic coefficients of variations were close to each other for all traits except germination capacity. Germination capacity exhibited positive significant correlation with 100-seed weight both at genotypic (r = 0.762) and phenotypic (r = 0.548) level and 100- seed weight expressed positive significant correlation with oil content both at genotypic (r = 0.604) and phenotypic (r = 0.573) level. In conclusion, oil content and 100-seed weight are under strong genetic control hence improvement in these characters can bring improvement in germination capacity.